Whole-cell fluorescence in situ hybridization of harmful diatom pseudo-nitzschia (bacilliariophyceae) in Kuching Estuary - Yong, Hwa Lin (Universiti Malaysia Sarawak, UNIMAS, 2012)
Pennate diatom of the genus Pseudo-nitzschia is recognized as causative organisms producing domoic acid (DA), a neurotoxin associated with amnesic shellfish poisoning (ASP). Conventional methods using light and electron microscopes such as TEM and SEM are undoubtedly useful for Pseudo-nitzschia species identification. Nevertheless, this requires taxonomic expertise, and EM preparations are laborious. Wholecell fluorescence in-situ hybridization (FISH) has been developed using the molecular approach as a rapid detection tool that eases the detection of Pseudo-nitzschia in natural population. In this study, whole-cell FISH was applied to investigate the distribution of Pseudo-nitzschia species in Kuching estuary. Field sampling was undertaken at Santubong and Samariang estuaries fortnightly from September 2011 till April 2012. The results showed that extremely low abundance of Pseudo-nitzschia cells in both locations. Largesubunit ribosomal RNA oligonucleotide probes for P. circumpora (L-S-Pcir-52-A-18), P. caciantha (L-SPcac-38-A-18), and P. pungens (L-S-Ppun-405-A-18) were designed in silico. Synthesized P. pungens and P. caciantha probes were subsequently optimized using centrifugation-based whole-cell FISH. The probes were tested on culture and spike natural samples, and the results showed that both probes are species-specific. This molecular species detection technique is proven to be useful particularly in harmful algal monitoring.